Understanding tuberculosis - Aguinaldo, F. (Quezon City MMA Publications, 2002)
Aguinaldo aims to give basic information to inspire awareness in the public for prevention of the disease. This book gives general information about tuberculosis, including its symptoms, diagnosis, progression and treatment. This book may be used by students and professors as a resource material for studying tuberculosis. This manual is also recommended for use of the general public.
Keywords: Tuberculosis -- Handbooks, manuals, etc; Tuberculosis -- Prevention